Microwave-assisted hydrothermal synthesis and energy storage application of nickel-aluminum layered double hydroxide-graphene foam nanocomposites - Manyala, Ncholu I. (University of Pretoria, 2024)
Dissertation (MSc (Physics))--University of Pretoria, 2015.